Narrowing Diurnal Temperature Amplitude Alters Carbon Tradeoff and Reduces Growth in C4 Crop Sorghum - Sunoj, V. S. John; Prasad, P. V. Vara; Ciampitti, Ignacio A.; Maswada, Hanafey F. (Frontiers in Plant Science, 2020)
Effect of diurnal temperature amplitude on carbon tradeoff (photosynthesis versus respiration) and growth are not well documented in C4 crops, especially under changing temperatures of light (daytime) and dark (nighttime) phases in 24 hours of a day. Fluctuations in daytime and nighttime temperatures due to climate change narrows diurnal temperature amplitude which can alter circadian rhythms in plant, thus influence the ability of plants to cope with temperature changes and cause contradictory responses in carbon tradeoff, particularly in night respiration during dark phase, and growth. Sorghum (Sorghum bicolor (L.) Moench) is a key C4 cereal crop grown in high temperature challenging agro-climatic regions. Hence, it is important to understand its response to diurnal temperature amplitude. This is the first systematic investigation using controlled environmental facility to monitor the response of sorghum to different diurnal temperature amplitudes with same mean temperature. Two sorghum hybrids (DK 53 and DK 28E) were grown under optimum (27°C) and high (35°C) mean temperatures with three different diurnal temperature amplitudes (2°C, 10°C and 18°C) accomplished by modulating daytime and nighttime temperatures (optimum daytime and nighttime temperatures [ODNT]: 28/26, 32/22 and 36/18°C and high daytime and nighttime temperatures [HDNT]: 36/34, 40/30 and 44/26°C). After exposure to different temperature conditions, total soluble sugars, starch, total leaf area and biomass were reduced, while night respiration and specific leaf area were increased with narrowing of diurnal temperature amplitude (18°C to 2°C) of HDNT followed by ODNT. However, there was no influence on photosynthesis across different ODNT and HDNT. Contradiction in response of foliar gas exchange and growth suggests higher contribution of night respiration for maintenance rather than growth with narrowing of diurnal temperature amplitude of ODNT and HDNT. Results imply that diurnal temperature amplitude has immense impact on the carbon tradeoff and growth, regardless of hybrid variation. Hence, diurnal temperature amplitude and night respiration should be considered while quantifying response and screening for high temperature tolerance in sorghum genotypes and comprehensive understanding of dark phase mechanisms which are coupled with stress response can further strengthen screening procedures.